2020
DOI: 10.17109/azh.66.4.309.2020
|View full text |Cite
|
Sign up to set email alerts
|

Natural and artificial scents do not increase egg rejection rates of model brood parasitic eggs by American robins (Turdus migratorius)

Abstract: Hosts of obligate avian brood parasites can diminish or eliminate the costs of parasitism by rejecting foreign eggs from the nests. A vast literature demonstrates that visual and/or tactile cues can be used to recognize and reject natural or model eggs from the nests of diverse host species. However, data on olfaction-based potential egg recognition cues are both sparse and equivocal: experimentally-applied, naturally-relevant (heterospecific, including parasitic) scents do not appear to increase egg rejection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…Few studies have examined how the scent of the parasitic eggs can inform rejection decisions by rejecter hosts (but see Rasmussen 2013; Soler et al., 2014). The only study that has tested the effect of scent in robins found no effect of scent treatments (artificial: citrus, natural: cowbird cloacal lavage, control: solvent only) on egg rejection responses (Hauber, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Few studies have examined how the scent of the parasitic eggs can inform rejection decisions by rejecter hosts (but see Rasmussen 2013; Soler et al., 2014). The only study that has tested the effect of scent in robins found no effect of scent treatments (artificial: citrus, natural: cowbird cloacal lavage, control: solvent only) on egg rejection responses (Hauber, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Little is known about the general role of olfactory cues in anti‐parasitic egg recognition (but see Rasmussen 2013; Soler et al., 2014). From our review of robins' responses to (model) cowbird eggs, olfaction did not influence egg rejection in robins; in the only study analyzing olfactory cues that we sourced for this review, neither unnatural scents of model eggs (citrus, human) nor a natural scent (cowbird cloacal lavage) affected egg rejection in robins (Hauber, 2020). This was contrary to findings in magpies, where Soler et al., (2014) found that the unnatural scent treatment of human handling or tobacco smoke both significantly increased egg rejection rates, although natural scent treatments of uropygial secretion of cuckoos and cloacal scents of cuckoos and magpies did not do so.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only partly vision-related traits such as egg shape and size showed small effects and the effect of other, also potentially partly tactile traits represented by natural vs. model materials, was negligible. Other hypothesized recognition cues, such as egg odor (e.g., Soler et al, 2014;Hauber, 2020) or weight (Ruiz-Raya et al, 2015) could not be statistically analyzed due to insufficient number of published reports (Figure 5). Therefore, our first recommendation is that more such studies address the potential roles of tactile-only or olfactory cued egg rejection behaviors in varied hosts of diverse avian brood parasites (also see Turner and Hauber, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…As part of our ongoing studies of robins and their anti-parasitic egg rejection behaviors (e.g., Abolins-Abols & Hauber, 2020;Hauber, 2020), from 2018 to 2020, we located 1,170 robin nests at a commercial deciduous tree farm from April to July in Champaign County, Illinois, USA, including 24 robin nests built directly on the ground.…”
Section: Me Thods and Re Sultsmentioning
confidence: 99%